Risk analysis of crop rotation systems with triticale, under no-tillage - Pereira dos Santos, Henrique; Ambrosi, Ivo; Cesar Barreneche Lhamby, Julio; Carlos Baier, Augusto (Pesquisa Agropecuaria Brasileira, 1998)
During five years (1987 to 1991), in Passo Fundo, RS, Brazil, the effects of crop rotation systems with triticale were assessed. Five systems for triticale were studied: system I (triticale/soybean), system II (triticale/soybean and black oats/soybean), system III (triticale/soybean and common vetch/corn), system IV (triticale/soybean, common vetch/corn, and black oats/soybean), and V (triticale/soybean, triticale/soybean, common vetch/corn, and black oats/soybean). In 1990, black oats was replaced by white oats in systems II, IV, and system V. A randomized complete block design with three replications was used. Risk analysis over that period is presented in this paper. Two types of analysis were aplied on the net return of the systems: mean-variance analysis and risk analysis (safety-first and stochastic dominance). Identification of the best system studied through mean-variance analysis was not feasible. Through the stochastic dominance method, the system III, during the first period (1987 to 1989), and the system II, over the second period (1990 to 1991), were the best production alternatives to be offered to the farmers from both profit and lower risk standpoints.